Health implications of plant-based meat analogs - Kumar, Pavan; Verma, Akhilesh K.; Umaraw, Pramila; Mehta, Nitin; Ismail-Fitry, Mohammad Rashedi; Narnoliya, Lokesh Kumar; Sharma, Neelesh; Sazili, Awis Qurni (Elsevier, 2024)
With increasing awareness and concerns related to the adverse environmental impact of conventional methods for meat production, animal welfare issues, and sustainability of food supply, plant-based meat analogs are widely regarded as potential candidates for replacing meat as future protein-rich foods. The plant-based meat analogs are developed by converting readily available and cheap vegetable proteins into products imitating meat in textural, organoleptic attributes, and nutritional characteristics. During the development of these products, a wide range of compounds such as plant proteins, carbohydrates, lipids, coloring agents, flavorings, spices, vitamins, and minerals are incorporated to impart meat-like attributes. The preferred composition and nutritive value of these products could be easily modified by selecting the appropriate ingredients and processing technologies. However, the high-end processing with the incorporation of a range of ingredients and the absence of some crucial bioactive compounds/metabolites in these products remain major concerns in the food industry. Its health implications and sustainability of production are the key issues that need to be discussed and analyzed before taking this transition away from animal-based products. Though the shift is not expected to be total, it could serve as an alternative to flexitarians and vegans.